â€œBRTTâ€ (Clean, Neat, Orderly, Organized) Program as a Pioneer of Daarut Tauhid Santri with Ecological Intelligence - Mutiara, Dea (International Journal Pedagogy of Social Studies, 2020)
Daarut Tauhid as one of the educational institutions that study religion proves that an islamic boarding school does not only deepen the Holy Qurâ€™an and hadith; but also does real activities in the society. Researchers are interested in capturing the process of implementing the "BRTT" program to the ecological intelligence of the Santri[1] of Daarut Tauhid. This research uses a qualitative approach with a case study method. The subjects of this study include the santri from Daarut Tauhid, the Quality Control Team and Daarut Tauhid Principal. The data are collected through observation, interviews, and documentation. The results of this study indicate that the background of implementing this program is the desire to make islamic boarding schools as pioneers of a clean, neat, orderly, and organized attitude to its santri and to the people who live nearby. The process of implementing the BRTT program is carried out in two categories: internally and externally. The obstacles encountered in the implementation of the BRTT program were self-habit constraints and fatigueness. The factors that influence the students in being disciplined in implementing BRTT are self-consciousness and environmental habit. The ecological intelligence of the students of Daarut Tauhid consists of seven aspects: (1) understanding environmental issues and problems from the perspective of ecological balance and sustainability, (2) conducting BRTT starting with a rule, mandatory policies which gradually become a habit and are inherent in self, (3) ways of solving problems creatively and applying knowledge in a new situation (ecological context), (4) oftenly assess the impact and the effects of human actions and technology on the environment, (5) oftenly take into account of the long-term consequences in taking a decisions (environmental context), (6) knowing indicators of clean and healthy living behavior, also (7) ways to give attention, empathy, and care for others and other living things.[1] Santri is the students of islamic boarding school